Examining the perceived impact of an ethics workshop on interprofessional values and teamwork. Issue 5 (3rd September 2017) - Manspeaker, Sarah A.; Donoso Brown, Elena V.; Wallace, Sarah E.; DiBartola, Leesa; Morgan, Allison
ABSTRACT: Interprofessional education (IPE) is a vital component of healthcare education yet challenges to implementation persist. This study aimed to evaluate the perceived impact of an ethics-based IPE workshop designed for professional phase healthcare students enrolled in athletic training, health management systems, occupational therapy, physical therapy, physician assistant studies, and speech-language pathology programmes at one university. A pre/post-test cohort study was conducted to evaluate the impact of the workshop on interprofessional values and teamwork. Findings from the 61 students who completed both pre- and post-programme evaluation surveys suggest that the ethics-based workshop was successful in improving perceived confidence as related to the workshop objectives and strengthened positive perceptions of IPE as evaluated by the Student Perceptions of Interprofessional Clinical Education-Revised (SPICE-R). Analysis of responses to open-ended reflection questions after the workshop suggest that student participants perceived changes in understanding related to multiple areas of IPE. These results suggest that an ethics-based workshop using case-based collaborative pedagogy may be an effective mechanism for delivery of IPE-oriented information resulting in greater student confidence and understanding of IPE competencies.